STRATEGI PENGEMBANGAN POTENSI PERKEBUNAN KOPI KABUPATEN MAGELANG - Rahardjo, Budi; Ikhwan, Khairul; Verawati, Dian Marlina; Novitaningtyas, Ivo (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2022)
Coffee is a plantation commodity that has high economic value. Indonesian coffee consumption continues to increase due to the shifting trend of drinking coffee in society. Magelang Regency as a coffee producer has the potential to be developed. By considering the area of coffee plantations and the condition of Magelang Regency as a super-priority tourist destination, a strategy is needed to develop the potential of coffee as a good economically viable product. Thus, this study aims to analyze the coffee plantation development strategy in Magelang Regency through the Strength, Weakness, Opportunities, and Threats (SWOT) matrix. The results showed that the condition of coffee plantations in Magelang Regency experienced a decrease in land area from year to year. Strategy analysis in an effort to develop the potential of coffee plantations in Magelang Regency through SWOT analysis is in quadrant III. The strategy that can be implemented is a turn-around strategy through efforts to increase knowledge of cultivation, postharvest, and technology for coffee farmers, and rejuvenating coffee plants that are entering an unproductive period.